THE CONCEPT AND SIGNIFICANCE OF FINANCIAL INVESTIGATION: INTERNATIONAL STANDARDS AND FOREIGN EXPERIENCE, ANALYSIS OF NATIONAL LEGISLATION - R.Kh.Rakhimov (American Journals, 2023)
The article is devoted to the analysis of studies by foreign scholars regarding the theory of financial investigation, in particular, the term “financial investigations”. The article discloses the international experience in the field of regulation of financial investigations and the use of this concept in national legislation.
Keywords: FATF, financial investigation, proceeds of crime, criminal activity, money laundering, terrorist financing, predicate offense, money, property, seizure, confiscation, forensic.